5,9,11-Trihydroxy-10-(2″-hydroxy-3″-methylbut-3″-en-1-yl)-2,2-dimethyl-3-(2′-methylbut-3′-en-2′-yl)-2H,12H-pyrano[2,3-a]xanthen-12-one from Calophyllum pseudomole - Tanjung, Mulyadi (MDPI AG, Basel, Switzerland, 2017)
Abstract: A new pyranocoumarin, namely 5,9,11-trihydroxy-10-(2″-hydroxy-3″-methylbut- 3″en-1-yl)-2,2-dimethyl-3-(2′-methylbut-3′-en-2′-yl)-2H,12H-pyrano[2,3-a]xanthen-12-one 1, was isolated from the stem barkof Calophyllum pesudomole. The structure of compound 1 was elucidated based on its ultaraviolet (UV); infrared (IR); high resolution electro spray ionization mass spectrometry (HRESIMS); 1D and 2D nuclear magnetic resonance (NMR) spectral data.